The use of Vitally Active Cellulose Membranes for the Reduction of Pathogenic Bacterial Count in White Cheese - Kamona, Zaid K.; Alshaikh Daher, Amer Abdulrahman; Al Shamary, Elham Ismael (Iraqi Journal of Science, 2021)
This study was designed to evaluate the effects of cellulose membranes produced by Acetobacter xylinum bacteria, after enrichment of the growth media with Alzahdy palm dates syrup to enhance cellulose production for reducing the contamination of locally-produced white cheese with pathogenic bacteria. Cellulose was vitally activated by incubation with both probiotics Lactobacillus acidophilus and Lactobacillus plantarum and the effectiveness of the produced cellulose membranes was measured by studying six characteristics: elongation, tensile strength, membrane rupture, permeability to oxygen, permeability to water vapor, and thickness (mm). The produced membranes showed remarkable functionality and characteristics for all studied tests. The results indicate that the cellulose membranes showed high antibacterial activity after incubation with Lactobacillus acidophilus and Lactobacillus plantarum for 24 and 48 hours against five different pathogenic bacteria, namely E. coli, S. aureus, Pseudomonas sp., B. cereus and S. typhymurim. Moreover, a positive result was obtained by reducing the number of these pathogenic bacteria after treating the white cheese with the produced cellulose membranes.